2015
DOI: 10.1051/ocl/2014053
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of sunflower oil and linseed oil as dietary ingredient for gilthead seabream (Sparus aurata) fingerlings

Abstract: -A feeding trial was conducted to define the optimal mixtures of either sunflower oil (SFO) or linseed oil (LO) with fish oil (FO), in fish meal (FM) based diets for gilthead seabream (Sparus aurata) fingerling, without significant effect on fish performance, fatty acid composition and liver structure. The trial lasted nine weeks with 420 fish (∼4.0 g) testing seven isonitrogenous (∼48% CP) and isolipidic (∼18% L) diets contained three incremental inclusions of either SFO or LO (40, 48, 56 g kg −1 ) and the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(62 reference statements)
0
4
0
1
Order By: Relevance
“…Moreover, Izquierdo et al proved that soybean or linseed and rapeseed oil substitution corrupt some textural characteristics of the fillets like succulence, hardness and stickiness (Izquierdo et al, 2005). Wassef et al (2015) evaluating sunflower oil and linseed oil as dietary ingredients for GSB fingerlings obtained that the use of sunflower oil is preferably then linseed oil as a complementary lipid resource. A previous study reported that FO replacement by cottonseed oil (CSO) up to 60% level had no detrimental effects on growth or nutritive utilization and composition in fish muscles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Izquierdo et al proved that soybean or linseed and rapeseed oil substitution corrupt some textural characteristics of the fillets like succulence, hardness and stickiness (Izquierdo et al, 2005). Wassef et al (2015) evaluating sunflower oil and linseed oil as dietary ingredients for GSB fingerlings obtained that the use of sunflower oil is preferably then linseed oil as a complementary lipid resource. A previous study reported that FO replacement by cottonseed oil (CSO) up to 60% level had no detrimental effects on growth or nutritive utilization and composition in fish muscles.…”
Section: Discussionmentioning
confidence: 99%
“…The main constraint for the use of VO in aquaculture feeds is the lack of omega‐3 (n‐3) long‐chain polyunsaturated fatty acids (LC‐PUFA), particularly EPA (20:5n‐3) and DHA (22:6n‐3) acids (Benedito‐Palos et al, 2008; Wassef et al, 2007, 2009, 2012, 2014, 2015). VO has also successfully replaced up to 60%–66% FO in diets for GSB, but higher substitution levels are difficult because of the specific requirement of GSB for LC‐PUFA, which are not present in VO (Benedito‐Palos et al, 2008; Caballero et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been achieved on other fish species to test the effect of plant oils in their diets, for instance [27] used linseed oil and sunflower oil in the diets of Sparusaurata fingerlings with an initial weight of 4 g, reared in tanks (50 litres) and fed on 46% protein and 18% lipids diets. Although, S. aurata is a carnivorous fish species, the sunflower diet provided the best growth, that could be explained by the presence of various animal protein resources in their diet.…”
Section: Growth Rate and Feed Conversionmentioning
confidence: 99%
“…A produção de farinha e OP além de ser considerada uma atividade de alto impacto, uma vez que são produzidos a partir dos estoques naturais, também possuem elevado custo e alta variabilidade nutricional, interferindo na produção das dietas para animais marinhos (Silva et al, 2010). Um esforço considerável vem sendo realizado desde a década de 1990 com o intuito de substituir o OP por óleos alternativos, geralmente de origem vegetal, como o óleo de linhaça (OL) (Bell et al, 1993;Izquierdo et al, 2003;Wassef et al, 2015), óleo de soja (OS) (Brown et al, 1997;Lee et al, 2000;Grisdale-Helland et al, 2002), óleo de canola (OCA) (Glencross, 2003;Francis et al, 2007;Huang et al, 2007). Alguns trabalhos encontraram resultados satisfatórios utilizando diferentes níveis de substituição de OP por óleos vegetais (OV).…”
Section: áCidos Graxos -Estrutura Classificação E Funçõesunclassified